(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Our main purpose is to introduce the concepts of upper and lower sβ()-continuous multifunctions. In particular, some characterizations of upper and lower sβ()-continuous multifunctions are investigated. Moreover, the relationships between sβ()-continuous multifunctions and almost sβ()-continuous multifunctions are discussed.